2023
DOI: 10.32604/csse.2023.034092
|View full text |Cite
|
Sign up to set email alerts
|

Eye Detection-Based Deep Belief Neural Networks and Speeded-Up Robust Feature Algorithm

Abstract: The ability to detect and localize the human eye is critical for use in security applications and human identification and verification systems. This is because eye recognition algorithms have multiple challenges, such as multi-pose variations, ocular parts, and illumination. Moreover, the modern security applications fail to detect facial expressions from eye images. In this paper, a Speeded-Up Roust Feature (SURF) Algorithm was utilized to localize the face images of the enrolled subjects. We highlighted on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…For this reason, some research studies have suggested integrating chaos into BOA for avoiding problems in performance and boosting optimization efficacy. In non-linear dynamic systems, a bounded dynamic behavior named chaos can be described by a chaos map that produces a small range of random numbers regarding the given conditions [28,29]. Through assessing Eq.…”
Section: Feature Extraction Using Optimal Inception V3 Modelmentioning
confidence: 99%
“…For this reason, some research studies have suggested integrating chaos into BOA for avoiding problems in performance and boosting optimization efficacy. In non-linear dynamic systems, a bounded dynamic behavior named chaos can be described by a chaos map that produces a small range of random numbers regarding the given conditions [28,29]. Through assessing Eq.…”
Section: Feature Extraction Using Optimal Inception V3 Modelmentioning
confidence: 99%